Selected health behaviours in professionally active men and women - Chuchra, Maria; Gorbaniuk, Julia (Polish Journal of Public Health, 2018)
Introduction. Women suffer from health problems more often and for a longer time, however it is generally men who die earlier.Aim. The aim of this work is to compare the selected health behaviours of working men and women.Material and methods. The research included 100 men and 100 women. The respondents were tested with the matched pair-selection method, taking into consideration four variables: place of residence, level of education, marital status, and age. The survey questionnaire was used.Results. Men and women show similarities with respect to some health behaviours, showing significant differences (amount and kind of alcoholic beverages drunk, regularity of preventive checks) in relation to others.Conclusions. Women’s health behaviours are to be evaluated more positively than men’s. Both men and women require intensive educational activities concerning the effects of anti-health behaviours, especially bad eating habits and irregularity of preventive checks.